PLATO’S REPUBLIC AND LEADERSHIP QUESTIONS IN NIGERIA: A PHILOSOPHICAL INTERROGATION OF GOVERNANCE, JUSTICE, AND POLITICAL AUTHORITY - Samuel Kayode, Babatunde de; Danladi Fwa, Yakubu; Sunday, Kenneth (African Journal of Social and Behavioural Sciences, 2026)
his study examines leadership challenges in Nigeria through the philosophical lens of Plato’s Republic. Despite over two decades of democratic rule, Nigeria continues to experience corruption, weak institutions, and declining public trust, raising concerns about the ethical foundations of its leadership. The study analysed Plato’s conception of ideal leadership and justice, the nature of political leadership in Nigeria with emphasis on corruption and elite dominance, and assessed the relevance of Platonic ideas to contemporary governance. Anchored on elite theory, the study explained how political power is concentrated among a small ruling class, contrasting this with Plato’s ideal of morally and intellectually grounded leaders. A qualitative, non-empirical methodology was adopted, relying on critical textual analysis of philosophical and contemporary scholarly sources, with thematic and normative evaluation. Findings revealed a significant gap between Platonic ideals and Nigerian realities, as leadership is largely driven by self-interest, patronage, and systemic corruption. Elite dominance, institutional weakness, and compromised anti-corruption mechanisms further undermine accountability and democratic development. However, Plato’s emphasis on merit, ethical leadership, and the common good remains relevant as a normative guide. The study concluded that Nigeria’s leadership crisis stems from ethical and structural deficiencies. It recommended integrating civic and ethical education into curricula, strengthening anti-corruption institutions, enforcing merit-based leadership selection, and promoting active civic engagement to foster accountable and just governance.